Multicolour imaging for the detection of polypoidal choroidal vasculopathy and age-related macular degeneration - Tan, Colin Siang Hui (2021)
Importance: Multicolour is a new imaging technology and its sensitivity for detecting polypoidal choroidal vasculopathy (PCV) and age-related macular degeneration (AMD) has not been well described. Background: To evaluate the accuracy of multicolour imaging compared to colour fundus photography (CFP) in differentiating AMD and PCV from normal eyes, and in detecting PCV. Design: Prospective cohort study at a tertiary referral centre. Participants: Fifty consecutive patients with PCV or AMD. Methods: Standardized multimodal imaging, including CFP, multicolour imaging, and fluorescein and indocyanine green angiography, were graded by a Central Reading Center using standardized grading protocols. Main outcomes and measures: Sensitivity, specificity, positive and negative predictive values (PPV and NPV). Results: Of 100 eyes, 44 had PCV, 33 had AMD, and 23 were normal. Multicolour imaging had higher specificity (73.9% vs 52.2%) and NPV (94% vs 85.7%) compared to CFP for detecting all types of AMD. For the detection of PCV, multicolour had higher sensitivity (86.4% vs 59.1%) and NPV (89.3% vs 74.3%). Polypoidal lesions were detected in 39 of 44 eyes (88.6%) using multicolour imaging, while the branching vascular network (BVN) was detected in 16 of 44 eyes (36.4%). Using BVN as a parameter, infrared imaging specificity and PPV for detecting PCV were 96.6% and 88.9%, respectively. Conclusions: Multicolour imaging is superior to standard CFP in differentiating AMD and PCV from normal eyes, and in detecting features of PCV. Specific features seen on multicolour imaging can alert ophthalmologists to the likely presence of these diseases so that additional definitive investigations can be performed.